Brief overview of the international flower market, its state and development under present-day economic conditions - Khodarchenko, V. (Applied Studies in Agribusiness and Commerce, 2010)
The research of international flower market was conducted in this article.A big attention was paid to the main countries which are suppliers and importers of flowers and plants including their shares in the world flower production. The impact of financial crisis on this economic sector and inequality in consumption level of different countries were observed.